2006
DOI: 10.1038/nature04655
|View full text |Cite
|
Sign up to set email alerts
|

Independent evolution of bitter-taste sensitivity in humans and chimpanzees

Abstract: It was reported over 65 years ago that chimpanzees, like humans, vary in taste sensitivity to the bitter compound phenylthiocarbamide (PTC). This was suggested to be the result of a shared balanced polymorphism, defining the first, and now classic, example of the effects of balancing selection in great apes. In humans, variable PTC sensitivity is largely controlled by the segregation of two common alleles at the TAS2R38 locus, which encode receptor variants with different ligand affinities. Here we show that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
86
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(102 citation statements)
references
References 30 publications
14
86
1
1
Order By: Relevance
“…Another case of convergent evolution of taste was found in the Tas2r38 receptor gene. Mutations in the Tas2r38 gene have resulted in independent loss of phenylthiocarbamide sensitivity in some humans, chimpanzees, and macaques (30,31). Notably, the mutations in chimpanzees and macaques are start codon mutations, resembling the case with sea lion and fur seal Tas1r2s (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Another case of convergent evolution of taste was found in the Tas2r38 receptor gene. Mutations in the Tas2r38 gene have resulted in independent loss of phenylthiocarbamide sensitivity in some humans, chimpanzees, and macaques (30,31). Notably, the mutations in chimpanzees and macaques are start codon mutations, resembling the case with sea lion and fur seal Tas1r2s (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, exchanging tryptophan in position 201 for leucine or phenylalanine caused severely reduced PTC responsiveness and, practically, a loss of activation by PROP. Intriguingly, Trp-5.46 is found only in the haplorrhine primate clade including human and chimpanzee, which exhibit exquisitely PTC-as well as PROP-sensitive TAS2R38 receptors (33,66). Hence, it seems that PTC/PROP-sensitive TAS2R38 evolved within the Primate order in the haplorrhine branch.…”
Section: Substancementioning
confidence: 99%
“…Furthermore, Wooding and coworkers (237) showed that PTC taste sensitivity in chimpanzees is associated with different amino acid haplotypes at the TAS2R38 gene compared to humans, implying a unique origin of the taster/nontaster variants in humans and chimpanzees.…”
Section: Dietary Adaptations In African Populationsmentioning
confidence: 99%
“…For example, the ability to taste phenylthiocarbamide (PTC), a synthetic bitter substance, is a highly variable trait in humans (83). Although several TAS2R loci contribute to variability in PTC taste perception (54,55), 50%--85% of the phenotypic variance in PTC sensitivity is attributed to variation at the TAS2R38 gene (237).. Studies have identified three amino acid substitutions at TAS2R38 that are in nearly complete LD in non-African populations and that form two common amino acid haplotypes (a taster haplotype PAV and a nontaster haplotype AVI; PAV is dominant). Furthermore, considerably more haplotype variability has been observed in Africa (M.C.…”
Section: Dietary Adaptations In African Populationsmentioning
confidence: 99%